The Influence of Diet Composition on Fitness of the Blue Crab, Callinectes sapidus. - Benjamin A Belgrad; Blaine D Griffen (PLoS ONE, 2016)
The physiological condition and fecundity of an organism is frequently controlled by diet. As changes in environmental conditions often cause organisms to alter their foraging behavior, a comprehensive understanding of how diet influences the fitness of an individual is central to predicting the effect of environmental change on population dynamics. We experimentally manipulated the diet of the economically and ecologically important blue crab, Callinectes sapidus, to approximate the effects of a dietary shift from primarily animal to plant tissue, a phenomenon commonly documented in crabs. Crabs whose diet consisted exclusively of animal tissue had markedly lower mortality and consumed substantially more food than crabs whose diet consisted exclusively of seaweed. The quantity of food consumed had a significant positive influence on reproductive effort and long-term energy stores. Additionally, seaweed diets produced a three-fold decrease in hepatopancreas lipid content and a simultaneous two-fold increase in crab aggression when compared to an animal diet. Our results reveal that the consumption of animal tissue substantially enhanced C. sapidus fitness, and suggest that a dietary shift to plant tissue may reduce crab population growth by decreasing fecundity as well as increasing mortality. This study has implications for C. sapidus fisheries.